Cancer, Benign Gynecology, and Sexual Function—Issues and Answers. Issue 4 (1st April 2016) - Bennett, Nelson; Incrocci, Luca; Baldwin, David; Hackett, Geoff; El-Zawahry, Ahmed; Graziottin, Alessandra; Lukasiewicz, Monika; McVary, Kevin; Sato, Yoshikazu; Krychman, Michael
ABSTRACT: Introduction: The diagnosis, treatment, and survivorship of cancer have a profound effect on the quality of life and psychological well-being of men and women. Indeed, the perturbation of sexual function because of neoplasm has far-reaching implications. Aims: To explore the prevalence, pathophysiology, and treatment of sexual issues in persons with cancer and offer evidence-based recommendations regarding optimal prevention and treatment strategies. Methods: A committee of multidisciplinary specialists was formed as part of the larger International Sexual Medicine Consultation working with urologic and sexual medicine societies over a 1-year period to review the result of chronic-illness management on sexual function and satisfaction. The aims, goals, data collection techniques, and report format were defined by a central committee. Main Outcomes Measures: Expert consensus was based on evidence-based medical and psychosocial literature review, extensive group discussion, and an open presentation with a substantial discussion period. Results: This summary evaluates contemporary literature concerning the prevalence, pathophysiology, and psychological impact of cancer diagnosis and treatment on sexual dysfunction. Evidence-based recommendations and guidelines for evaluation and management are presented. Conclusion: The diagnosis and treatment of cancer have a significant negative impact on sexual function and satisfaction. Comprehension of baseline sexual function, role of psychological supports, and available treatment options could attenuate the heavy burden of decreased sexual function.